Jaminan Kepastian Hukum Bagi Anak yang Lahir dari Perkawinan Campuran Berdasarkan Undang-Undang Nomor 12 Tahun 2006 tentang Kewarganegaraan Republik Indonesia - Fara Puspita Aqila Ningrum (Jurnal Hukum Lex Generalis, 2025)
Mixed marriages involving Indonesian citizens (WNI) and foreign citizens (WNA) raise legal issues related to the citizenship status of the resulting children. Law Number 12/2006 on Citizenship of the Republic of Indonesia has regulated the mechanism of citizenship of children resulting from mixed marriages, but its implementation still faces various obstacles. This research aims to analyze the legal certainty for children from mixed marriages with a normative juridical approach that examines laws and regulations and related case studies. The results show that although regulations have provided space for limited dual citizenship status up to the age of 18, there are various obstacles in implementation, such as lack of public understanding, bureaucratic complexity, and differences in legal principles between Indonesia and the foreign partner's country. Therefore, policy reform, increased coordination between government agencies, and broader education for the public are needed to ensure optimal legal protection for children from mixed marriages.